2017
DOI: 10.1128/genomea.01374-16
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Southern tomato virus in Asymptomatic Tomato ‘Sweet Hearts’

Abstract: The genome sequence of Southern tomato virus in asymptomatic Solanum lycopersicum ‘Sweet Hearts’ (STV-Florida) in Florida was assembled from small RNAs sequenced by Illumina RNA-seq. The STV-Florida genome shared 99.0 to 99.9% similarity with full genome sequences from Bangladesh, China, Mexico, and the United States (Mississippi and North Carolina).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
1
4
0
2
Order By: Relevance
“…For this purpose, an assay with tomato plants in virus single-, co- and triple-infections was performed. As expected, STV-single infected plants did not show any symptoms, corroborating the results that were obtained in previous research works [ 5 , 6 , 7 , 45 , 46 ]. In this assay, the STV titer remained constant over time (5–20 dpi) in single-infections, as reported previously [ 5 ], and the same occurred in in co- and triple-infections with CMV and PepMV The steady titer of STV during the infection contrasts with the majority of acute viruses, whose concentration varies, depending on the infection state [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…For this purpose, an assay with tomato plants in virus single-, co- and triple-infections was performed. As expected, STV-single infected plants did not show any symptoms, corroborating the results that were obtained in previous research works [ 5 , 6 , 7 , 45 , 46 ]. In this assay, the STV titer remained constant over time (5–20 dpi) in single-infections, as reported previously [ 5 ], and the same occurred in in co- and triple-infections with CMV and PepMV The steady titer of STV during the infection contrasts with the majority of acute viruses, whose concentration varies, depending on the infection state [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…The low production of STVderived vsiRNAs might explain the absence of plant symptoms in STV-infected tomato plants (Elvira-González et al 2018, Puchades et al 2017. Some authors reported also low concentrations of STV-derived sviRNAs which could change depending on coinfection with acute viruses (Fukuhara et al, 2019;Alcala-Briseno et al 2017, Muñoz-Adalia et al 2018, Niu et al 2017, Padmanabhan et al 2015a, Padmanabhan et al 2015b, Turco et al 2018, Xu et al 2017. Low productions of siRNAs have been reported for some persistent plant virus such as totiviruses and partitiviruses which are phylogenetically related to STV (Sabanadzovic et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Asimismo, el análisis de HTS permitió el ensamblaje completo del genoma del STV (3.437 nt) y del BPEV (14.706 nt), lo que representa el primer reporte de estos virus en Colombia, para el cultivo del tomate. Para el caso del genoma de STV (MN095716), se identificaron dos ORF: el ORF 1, próximo al extremo 5´, que codifica para la proteína de cápside (CP) y el ORF 2, cercano al extremo 3´, con un cambio de marco de lectura +1, que codifica la RdRp; dicha secuencia compartió un porcentaje de identidad del 99%, con aislamientos procedentes de México (EF442780) y Estado Unidos (KX949574), lugares donde fue reportado, por primera vez, este virus (Sabanadzovic et al 2009); aunque desde entonces se ha informado de su detección en otros países, como Francia, España, Canadá y China (Alcalá et al 2017). De STV, solo se conoce su trasmisión, a través de semilla (Xu et al 2017); aunque la presencia de este virus, generalmente, se asocia con plantas asintomáticas, se ha reportado que induce síntomas, como decoloración en los frutos y reducción del tamaño de las plantas, en algunas variedades de tomate (Puchades et al 2017), por lo que la determinación de su efecto sobre la variedad Chonto, cultivada en Colombia, resulta prioritario, para evaluar su nivel de riesgo fitosanitario.…”
Section: Resultados Y Discusiónunclassified
“…Para el caso de las evaluaciones de semillas (SC y SNC) y sus respectivos brotes (BC y BNC), se detectó la presencia de todos los virus bajo estudio, con valores de Ct, muy cercanos a los detectados en las muestras de campo (Ct=25,2; SD=3,1 a Ct=32; SD=3,2). En el caso de SC, se destaca la detección de STV, como el virus de mayor prevalencia (80%) (Figura 3b), lo que no resulta inesperado, dado que se conoce de su transmisión vertical, a través de semilla de tomate, en niveles de hasta el 90% (Alcalá et al 2017). El segundo virus con mayor nivel de detección en el material SC correspondió al PYVV, que se detectó en el 73% de las muestras evaluadas, un valor muy alto para un virus que, hasta hace unos años, se consideraba solo de importancia en cultivos de papa de la región andina de Suramérica, donde se ha reportado que puede causar pérdidas hasta del 50% (Franco-Lara et al 2013).…”
Section: Resultados Y Discusiónunclassified